Three essays investigating the bequest intentions and expectations of older adults - Sommer, Matthew (Kansas State University, 2021)
Most wealth transfers occur at death, rather than during life, and children are the primary recipients of an inheritance upon the passing of a surviving spouse. Given these factors, this dissertation investigates older adults’ intentions and expectations of making a bequest to their children. The first essay explores the relationship between positive and negative social support with parents’ intentions of making a bequest. The second essay investigates a possible link between parents’ personality traits and the intention to make unequal bequests. The third essay researches the association between changes in wealth and a change in bequest expectations during and following the Great Recession. Data are collected from the Health and Retirement Study (HRS), a longitudinal study of over 43,000 U.S. adults over age 50. Several important findings have emerged from this research. First, a positive relationship exists between positive social support and bequest intentions but only conditioned upon having a will or trust. No relationship is found between negative social support and bequest intentions. Second, a negative relationship is found between conscientiousness and intentions to make unequal bequests. Also, this study finds a positive relationship between extraversion and agreeableness and intentions to make unequal bequests. Third, decreases in net worth are associated with a drop in bequest expectations during the Great Recession but increases in net worth are not associated with a rise in bequest expectations during the same period. Also, only respondents who experienced a net worth increase in the highest end of the distribution following the Great Recession are associated with a return to pre-recession bequest expectations. The findings of this research can be used by financial planners to help clients make important and highly personal decisions regarding the distribution of wealth to their children.
Keywords: Bequests